2005
DOI: 10.3168/jds.s0022-0302(05)72728-4
|View full text |Cite
|
Sign up to set email alerts
|

Monensin for Lactating Dairy Cows Grazing Mixed-Alfalfa Pasture and Supplemented with Partial Mixed Ration

Abstract: The effect of monensin on milk production was evaluated in 58 lactating Holstein cows (48 multiparous; 10 primiparous) grazing a mixed-alfalfa pasture and supplemented with a partial mixed ration in a completely randomized design with repeated measurements. Cows were paired by calving date, lactation number, previous lactation milk production, body weight, and body condition score and were assigned to one of 2 treatments: control or monensin. Cows on the monensin treatment received 2 monensin controlled-releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 23 publications
0
25
0
4
Order By: Relevance
“…Gallardo et al (2005) also reported positive effect by adding monensin, which increased milk yield by 4.0% in comparison to the control diet (27.7 vs. 26.6 kg/day, respectively). Eifert et al (2005) did not find any effect for milk yield when comparing the experimental diets, although the diet with monensin resulted in a higher value for milk yield (3.0%), in comparison with the control diet (26.5 vs. 26.6 kg/day, respectively).…”
Section: Resultsmentioning
confidence: 92%
“…Gallardo et al (2005) also reported positive effect by adding monensin, which increased milk yield by 4.0% in comparison to the control diet (27.7 vs. 26.6 kg/day, respectively). Eifert et al (2005) did not find any effect for milk yield when comparing the experimental diets, although the diet with monensin resulted in a higher value for milk yield (3.0%), in comparison with the control diet (26.5 vs. 26.6 kg/day, respectively).…”
Section: Resultsmentioning
confidence: 92%
“…The day after, the remaining pasture was measured. Consumption was estimated by the difference between offered and refused pasture (Gallardo et al 2005).…”
Section: Measurementsmentioning
confidence: 99%
“…The digestibility of forage is the highest in the vegetative stages due to variation in cell/ wall content and the stem/leaf ratio with increasing maturity (Terry and Tilley, 1964). The rate of decline in digestibility with increasing maturity also depends on annual average temperatures (Wilson et al, 1991) and on the species (Bargo et al, 2003;Gallardo et al, 2005).…”
mentioning
confidence: 99%